Effect of sputtering power on optical properties of prepared TiO2 thin films by thermal oxidation of sputtered Ti layers. (1st June 2017) - Astinchap, Bandar; Moradian, Rostam; Gholami, Katayon
Abstract: In this research, TiO2 thin films prepared via thermal oxidation of Ti layers were deposited by RF-magnetron sputtering method at three different sputtering powers. The effects of sputtering power on structure, surface and optical properties of TiO2 thin films grown on glass substrate were studied by X-ray diffraction (XRD), atomic force microscopic (AFM) and UV–visible spectrophotometer. The results reveal that, the structure of layers is changed from amorphous to crystalline at anatase phase by thermal oxidation of deposited Ti layers and rutile phase is formed when sputtering power is increased. The optical parameters: absorption coefficient, dielectric constants, extinction coefficient, refractive index, optical conductivity and dissipation factor are decreased with increase in sputtering power, but increase in optical band gap is observed. The roughness of thin films surface is affected by changes in sputtering power which is obtained by AFM images. Highlights: The TiO2 thin films were prepared by thermal oxidation of sputtering Ti layers. The effects of sputtering power on optical properties of TiO2 were investigated. The optical band gap and thickness increased with increasing sputtering power. The Urbach energy decreased by increasing sputtering power.